Anais Do Simpósio Brasileiro De Sistemas Elétricos 2020 2020
DOI: 10.48011/sbse.v1i1.2274
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Métodos de Análise Multicritério na Certificação de Lâmpadas LED

Abstract: As certificações de lâmpadas LED no país fazem parte do Programa Brasileiro de Etiquetagem (PBE), coordenado pelo Inmetro, e buscam fornecer informações sobre o desempenho dos produtos a fim de auxiliar a escolha dos consumidores e estimular a competitividade da indústria. Tendo em vista a necessidade de melhoria contínua dos processos de certificações de produtos no país, este trabalho busca apresentar por meio do método de análise multicritério TOPSIS um sistema de análise de lâmpadas LED. Para tanto, foi ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The tests executed were performed at LabLux, a laboratory of Federal Fluminense University (UFF-RJ/Brazil); it has INMETRO accreditation to perform conformity tests on lighting products and has a great experience in research related to lighting devices, as reported in several academic documents [13][14][15][16][17][18][19][20]. The laboratory has a shielded room for conducting and radiated EMC tests and a seasoning room to measure LED and fluorescent lamp life.…”
Section: Methodsmentioning
confidence: 99%
“…The tests executed were performed at LabLux, a laboratory of Federal Fluminense University (UFF-RJ/Brazil); it has INMETRO accreditation to perform conformity tests on lighting products and has a great experience in research related to lighting devices, as reported in several academic documents [13][14][15][16][17][18][19][20]. The laboratory has a shielded room for conducting and radiated EMC tests and a seasoning room to measure LED and fluorescent lamp life.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 gives a resume of the methodology scheme. 19 The measurements took into account the completeness and objectivity of the evaluated criteria in order to avoid redundancies. In addition, there were no dominance relationships between the alternatives.…”
Section: Work Structuring Approachmentioning
confidence: 99%